The terminology of clinical reasoning in health professions education: Implications and considerations. (2nd November 2019) - Young, Meredith; Thomas, Aliki; Gordon, David; Gruppen, Larry; Lubarsky, Stuart; Rencic, Joseph; Ballard, Tiffany; Holmboe, Eric; Da Silva, Ana; Ratcliffe, Temple; Schuwirth, Lambert; Durning, Steven J.
Abstract: Introduction: Clinical reasoning is considered to be at the core of health practice. Here, we report on the diversity and inferred meanings of the terms used to refer to clinical reasoning and consider implications for teaching and assessment. Methods: In the context of a Best Evidence Medical Education (BEME) review of 625 papers drawn from 18 health professions, we identified 110 terms for clinical reasoning. We focus on iterative categorization of these terms across three phases of coding and considerations for how terminology influences educational practices. Results: Following iterative coding with 5 team members, consensus was possible for 74, majority coding was possible for 16, and full team disagreement existed for 20 terms. Categories of terms included: purpose/goal of reasoning, outcome of reasoning, reasoning performance, reasoning processes, reasoning skills, and context of reasoning. Discussion: Findings suggest that terms used in reference to clinical reasoning are non-synonymous, not uniformly understood, and the level of agreement differed across terms. If the language we use to describe, to teach, or to assess clinical reasoning is not similarly understood across clinical teachers, program directors, and learners, this could lead to confusion regarding what the educational or assessment targets are for "clinical reasoning."